2022
DOI: 10.7150/jca.62652
|View full text |Cite
|
Sign up to set email alerts
|

miR-497-5p-RSPO2 axis inhibits cell growth and metastasis in glioblastoma

Abstract: Numerous studies have found a relationship between cancer formation and aberrant microRNA expression, however the biological significance of miR-497-5p in glioblastoma (GBM) is still unknown. Compared to normal brain glial cells, miR-497-5p expression in GBM tissues was substantially lower in our study. The microRNA miR-497-5p targets R-spondin 2 (RSPO2) only when it is present. RSPO2 silencing has the same effect on GBM cells as miR-497-5p silencing, as demonstrated before. Additional mechanistic investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These findings suggest that the cocktail might enhance the Wnt pathway by reducing the inhibitory effects of SFRP1, SFRP2, SFRP4, and MMP7 genes while simultaneously increasing the enhancing effect of the RSPO2 gene. RSPO2 is a Wnt agonist that enhances Wnt signaling by potentiating the interaction between Wnt ligands and Frizzled receptors (29,30). Research indicated that introducing recombinant human RSPO2 into a controlled environment led to a notable rise in the growth of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the cocktail might enhance the Wnt pathway by reducing the inhibitory effects of SFRP1, SFRP2, SFRP4, and MMP7 genes while simultaneously increasing the enhancing effect of the RSPO2 gene. RSPO2 is a Wnt agonist that enhances Wnt signaling by potentiating the interaction between Wnt ligands and Frizzled receptors (29,30). Research indicated that introducing recombinant human RSPO2 into a controlled environment led to a notable rise in the growth of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Xu Y et al also demonstrated that miR-493 exerts inhibitory effects on liver cancer development by suppressing the expression of SPON2, thereby attenuating the WNT signaling pathway (25). In their study, Kun Chen et al demonstrated that miR-497-5p effectively suppressed the expression of SPON2 in glioblastoma (GBM) tumors, thereby inhibiting the WNT/b-catenin signaling pathway and subsequently reducing cellular metastasis (7). Furthermore, Kang et al demonstrated a significant correlation between Notch signal transduction and SPON2 expression through cDNA microarrays and in vitro studies (16).…”
Section: Regulation Of Sponexpressionmentioning
confidence: 99%
“…In their study, Kun Chen et al. demonstrated that miR-497-5p effectively suppressed the expression of SPON2 in glioblastoma (GBM) tumors, thereby inhibiting the WNT/β-catenin signaling pathway and subsequently reducing cellular metastasis ( 7 ). Furthermore, Kang et al.…”
Section: Regulation Of Spon2 Expressionmentioning
confidence: 99%
See 2 more Smart Citations